Höhere Prävalenz von depressiven und ängstlichen Symptomen bei Früharthritispatienten im Vergleich zur Normalbevölkerung - Freier, D.; Englbrecht, Matthias; Höhne-Zimmer, V.; Detert, J.; Burmester, G. R. (Zeitschrift für Rheumatologie, 2019)
Background: Many studies and registry data confirm that depression, often associated with anxiety disorders is very often found in patients with rheumatoid arthritis (RA). To what extent these psychiatric disorders are already relevant at a very early stage of the disease, has currently not been adequately investigated. Methods: In this study 176 patients with early joint symptoms (<1 year) were surveyed in an early arthritis consultation (EAC). The hospital anxiety and depression scale (HADS) was completed by the patients to examine the prevalence of depressive and anxiety symptoms. The results were compared to normative data of the general German population and between the diagnosis groups. Results: With 47.7% the prevalence of global distress for EA patients was almost twice as high compared to the corresponding group from the general population. This was also confirmed for depressive and anxiety symptoms. The EA patients without confirmed evidence of musculoskeletal inflammatory rheumatic disease (RD) showed nearly the same point prevalence as patients with confirmed RD. In multiple logistic regression the health assessment questionnaire (HAQ) was positively associated with global distress (odds ratio, OR 3.63) while the visual analogue scale (VAS) for global disease activity was positively associated with symptoms of depression (OR 1.03). Female EA patients (OR 5.45) appear to have a higher probability for experiencing corresponding symptoms, whereas patients over 60 years old appear to have less anxiety than younger patients (OR 0.11). Conclusion: The high prevalence of symptoms of depression and anxiety in EA patients compared to the general population is a challenge for rheumatologists, orthopedists and general practitioners, particularly with respect to the differentiation of possible psychosomatic components in noninflammatory joint complaints. The results suggest that screening for psychiatric problems in patients with rheumatism should be evaluated as soon as possible as these can have a great impact on the perception of pain and physical functional status from the very beginning.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Anxiety; Depression; Early arthritis; HADS; Pain; Stress